y-(-3)=-2x-5

Simple and best practice solution for y-(-3)=-2x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-(-3)=-2x-5 equation:


Simplifying
y + -1(-3) = -2x + -5

Multiply -1 * -3
y + 3 = -2x + -5

Reorder the terms:
3 + y = -2x + -5

Reorder the terms:
3 + y = -5 + -2x

Solving
3 + y = -5 + -2x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + y = -5 + -3 + -2x

Combine like terms: 3 + -3 = 0
0 + y = -5 + -3 + -2x
y = -5 + -3 + -2x

Combine like terms: -5 + -3 = -8
y = -8 + -2x

Simplifying
y = -8 + -2x

See similar equations:

| 2(m-8)+9=3(4-m)-4 | | f(2c)=3(2c^2)+6(2c) | | -7.8=-1.4x+2 | | 6+4=120 | | -4p-5.2=11.1 | | 4x-13x-19=-73 | | f(x)=-7x^2+5x+7 | | 4x-45=3 | | f-12.3=-73.8 | | 4x-9+2x-1=14 | | -6m-6=24 | | 3x^2-36x-10=o | | 5x-6z=-17 | | 13x+8y=123 | | y-2=.75x-6 | | 6x+5+7x-3=28 | | 15+4n=9n | | -8x-22=23-5x | | 19x+1=x+37 | | -3(2x-6)=12 | | A^2-12a-13=0 | | 9(3)-(-6)+7= | | 2x-12=2+x | | 64c^2=25 | | 2(7+x)=-36 | | b/5+1/3=17 | | 11x=16500 | | (7+x)=-36 | | 5(v-7)=-45 | | y-13=-.8x-(-5) | | 0.6666x+1=x-4 | | -6t+t^2=0 |

Equations solver categories